Mitochondrial DNA Somatic Mutations (Point Mutations and Large Deletions) and Mitochondrial DNA Variants in Human Thyroid Pathology : A Study with Emphasis on Hürthle Cell Tumors - Máximo, Valdemar (American Society for Investigative Pathology, 2002)
In an attempt to progress in the understanding of the relationship of mitochondrial DNA (mtDNA) alterations and thyroid tumorigenesis, we studied the mtDNA in 79 benign and malignant tumors (43 Hürthle and 36 non-Hürthle cell neoplasms) and respective normal parenchyma. The mtDNA common deletion (CD) was evaluated by semiquantitative polymerase chain reaction. Somatic point mutations and sequence variants of mtDNA were searched for in 66 tumors (59 patients) and adjacent parenchyma by direct sequencing of 70% of the mitochondrial genome (including all of the 13 OXPHOS system genes). We detected 57 somatic mutations, mostly transitions, in 34 tumors and 253 sequence variants in 59 patients. Follicular and papillary carcinomas carried a significantly higher prevalence of nonsilent point mutations of complex I genes than adenomas. We also detected a significantly higher prevalence of complex I and complex IV sequence variants in the normal parenchyma adjacent to the malignant tumors. Every Hürthle cell tumor displayed a relatively high percentage (up to 16%) of mtDNA CD independently of the lesion’s histotype. The percentage of deleted mtDNA molecules was significantly higher in tumors with D-loop mutations than in mtDNA stable tumors. Sequence variants of the ATPase 6 gene, one of the complex V genes thought to play a role in mtDNA maintenance and integrity in yeast, were significantly more prevalent in patients with Hürthle cell tumors than in patients with non-Hürthle cell neoplasms. We conclude that mtDNA variants and mtDNA somatic mutations of complex I and complex IV genes seem to be involved in thyroid tumorigenesis. Germline polymorphisms of the ATPase 6 gene are associated with the occurrence of mtDNA CD, the hallmark of Hürthle cell tumors.